MICROPLASTICS ABUNDANCE AND UPTAKE BY MERETRIX LYRATA (HARD CLAM) IN MANGROVE FOREST - binti Shahul Hamid, Fauziah; Jia, Wang; Zakaria, Rozainah Mohamad (Journal of Engineering and Technological Sciences, 2020)
The aim of this study was to determine the abundance and distribution of microplastics in a mangrove ecosystem, while investigating its uptake by Meretrix lyrata. Microplastics were extracted from 10 L of mangrove sediment using a floatation method. Soft tissues of M. lyrata were digested and the microplastics were filtered and observed under a light microscope. Microplastics ranging from 21 µm to 100 µm were the most abundant in the mangrove layers at 936 ± 34 particles/kg (dry sediment) to 1,227 ± 55 particles/kg (dry sediment) (27.19% to 31.16% of the total quantity of recovered microplastics). The most abundant microplastics, with size from 5 µm to 1000 µm, were found in the deepest layer. M. lyrata accumulation of microplastics averaged at 0.35 ± 0.08 particles/g tissue and 0.23 ± 0.07 particles/g tissue (wet weight) before and after three-day depuration, respectively. Microplastics with size from 5 to 20 µm were the most commonly uptaken by the clams, averaging at 58% to 72% for pre-depuration and post-depuration, respectively. This study revealed that the most predominant size of microplastics in the sediment was 5 µm to 20 µm, which concurs with the results of the microplastics most commonly accumulated by M. lyrata. It is believed that microplastics accumulation in mangrove areas increases over time. On the other hand, the uptake rate of microplastics by Meretrix lyrata decreases over time, flushing microplastics from its system more frequently.